Readiness and Challenges of Higher Education to the New Normal – A Case of a Philippine Public University - Briones, Marie Claire B (ASEAN Journal of Basic and Higher Education, 2021)
Research on online learning has been focused on student readiness and few studies have been conducted among faculty members of higher education institutions. This study aimed to identify the readiness and challenges of faculty members in a Philippine Public University. Using an adapted but modified questionnaire from Gay (2016), 205 (53.39%) college faculty members from 9 satellite campuses participated after systematic sampling during mid-year 2021. Salient findings revealed that the faculty members are highly ready in online learning in terms of the following areas: technical, lifestyle, and pedagogical. Lifestyle readiness received the lowest mean rating while pedagogical readiness received the highest mean rating. Internet connection, beating deadlines, scoring student outputs, managing class time and other works, and stressful atmosphere during online class were found to top the challenges which the faculty members experienced in relation to the learning modality. The findings of the study have underscored the positivity among the faculty members in online instruction, and while issues found in their study could potentially retard the implementation of the Flexible Learning Modality at the University, it has to be understood that the University has no control on various challenges posed including intermittent power interruptions, poor internet connection, and learning spaces at home.